Characterization of a Pyrazolo[4, 3‐d]pyrimidine Inhibitor of Cyclin‐Dependent Kinases 2 and 5 and Aurora A With Pro‐Apoptotic and Anti‐Angiogenic Activity In Vitro. (16th September 2015) - Řezníčková, Eva; Weitensteiner, Sabine; Havlíček, Libor; Jorda, Radek; Gucký, Tomáš; Berka, Karel; Bazgier, Václav; Zahler, Stefan; Kryštof, Vladimír; Strnad, Miroslav
Abstract : Selective inhibitors of kinases that regulate the cell cycle, such as cyclin‐dependent kinases (CDKs) and aurora kinases, could potentially become powerful tools for the treatment of cancer. We prepared and studied a series of 3, 5, 7‐trisubstituted pyrazolo[4, 3‐ d ]pyrimidines, a new CDK inhibitor scaffold, to assess their CDK2 inhibitory and antiproliferative activities. A new compound, 2i, which preferentially inhibits CDK2, CDK5, and aurora A was identified. Both biochemical and cellular assays indicated that treatment with compound2i caused the downregulation of cyclins A and B, the dephosphorylation of histone H3 at Ser10, and the induction of mitochondrial apoptosis in the HCT‐116 colon cancer cell line. It also reduced migration as well as tube and lamellipodia formation in human endothelial cells. The kinase inhibitory profile of compound2i suggests that its anti‐angiogenic activity is linked to CDK5 inhibition. This dual mode of action involving apoptosis induction in cancer cells and the blocking of angiogenesis‐like activity in endothelial cells offers possible therapeutic potential. Abstract : We introduce novel pyrazolo[4, 3‐ d ]pyrimidine2i, which preferentially inhibits CDK2, CDK5 and aurora A. Treatment with2i causes the downregulation of cyclins A and B and the dephosphorylation of histone H3 at Ser10, induces apoptosis in HCT‐116 cancer cells and reduces angiogenesis‐like activity in endothelial cells.